(untitled) (Journal of the College of Basic Education, 2022)
In this study, the researcher proceeded to explain the Baghdad Pact and its emergence in 1955 AD, on Iran’s position on international alliances in the Middle East, from the discussions of regional countries; The emergence of an alliance, then the researcher in the study touched on the discussions and mediations of the regional and European countries; Because Iran joined the Baghdad Pact, in addition to Iran’s decision to join the alliance, which prompted the researcher to divide the study into three axes, preceded by an introduction and followed by a conclusion. Its formation and the mechanisms of its emergence during the era of the fifties of the last century, studied the second axis: known as "Iran’s policy of neutrality (international isolation) towards the alliance system (1953 - 1954)" The motives for adopting the Shah of Iran, Muhammad Reza Pahlavi, "the principle of neutrality - international isolation" about the policy of alliances and alliances With the countries of the West "Britain - France - the United States of America" ​​and the countries of the Middle East "Turkey - Iraq - Pakistan", and the third axis, marked "Iran’s accession to the Baghdad Pact in 1955 AD", touched upon the efforts of the Turkish and Iraqi states and the aforementioned Western countries and their repeated moves to pressure the Iran to join the Baghdad Pact until those countries achieved their goal, and following these axes a conclusion, which was represented in the most prominent: Iran’s accession to the Baghdad Pact in 1955 CE from the strength and solidity of the countries affiliated with the banner of this alliance, the study revealed The "British-American" goal of Iran’s joining the alliance, which was embodied in making it an impenetrable dam and a "military-defensive" shield against the movements of the Soviet Union, "Russia - communism" between the countries of the Middle East